2015
DOI: 10.15376/biores.11.1.1359-1368
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Water Absorption and its Influence on the Physical-Mechanical Properties of Bamboo-Bundle Laminated Veneer Lumber

Abstract: To investigate the possibility of using bamboo-bundle laminated veneer lumber (BLVL) as a cooling tower packing material, the water absorption rates, thickness swelling rates, and flexural properties of three different composite materials were studied. The BLVL was combined with either 12% or 24% phenol formaldehyde resin (PF), and the moso bamboo strips were exposed to water baths at three different temperatures (45, 65, and 85 °C) for 30 d. After the aging treatments, the 24%-BLVL samples showed lower water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The higher water absorption in the first days by the four-layer laminate is probably due to the higher panel thicknesses, wherein the wood surface area was higher than the interlaminar surface area, considering that the lateral ends of the laminates were not sealed with resin after the cutting process. In this sense, recent research corroborates how weight gain can mostly be ascribed to exposed wood, which is the most prone to absorbing water [ 9 , 35 ].…”
Section: Resultsmentioning
confidence: 74%
“…The higher water absorption in the first days by the four-layer laminate is probably due to the higher panel thicknesses, wherein the wood surface area was higher than the interlaminar surface area, considering that the lateral ends of the laminates were not sealed with resin after the cutting process. In this sense, recent research corroborates how weight gain can mostly be ascribed to exposed wood, which is the most prone to absorbing water [ 9 , 35 ].…”
Section: Resultsmentioning
confidence: 74%
“…Bamboo fibers are naturally porous and comprised of countless of hydroxyl groups, vascular bundles, and parenchyma tissues. Therefore, the hygroscopic nature of bamboo facilitated the higher moisture absorption levels (Li et al 2016) which increased the moisture absorption rate. Other studies found that the moisture absorption rate of silicone composites increased significantly as the fiber reinforcement percentage increased (Namitha et al 2013;Ismail et al 2019).…”
Section: Moisture Absorption Testmentioning
confidence: 99%
“…Higher temperatures tend to accelerate the water diffusion behaviour. It is believed that the phenomenon is due to quicker movement of water molecules at higher temperature [21,22]. At high temperature, there is also a chance of breakage of the addition H-bonds created in the cellulosic network [23].…”
Section: Water Sorption Behaviourmentioning
confidence: 99%